Loneliness in Leadership : Case Studies on Women Leaders - Amrah, Novita; Rahmadani, Vivi Gusrini; Ananda, Fahmi (Granada El-Fath, 2024)
This research aims to explore the meaning of loneliness in leadership and describe the dynamics of loneliness in leadership in terms of trigger factors, as well as the consequences felt by female civil servants in office, on the implementation of their duties. Qualitative research was chosen as the type of research used in this research. The method in this research uses a case study research method. The participants selected for this research were female civil servants who had the status of structural Administrator officials (echelon III) in regional government agencies within the North Sumatra Provincial Government. The number of participants to be able to obtain a holistic and comprehensive explanation of the loneliness experienced by female leaders was three (3) people. In this qualitative research, the data collection method used focuses on in-depth interviews and narratives. Apart from that, documentation methods or visual methods were also carried out and in collecting data in this research, primary data and secondary data were used. The research results show that all respondents experienced loneliness while serving as leaders.